PENGARUH PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS BERDASARKAN SELF EFFICACY SISWA - Radila Ingeswari, Putri; Bambang Sri Anggoro; Iip Sugiharta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by facts in the field which show that the mathematical communication skills of students at SMPN 06 Tulang Bawang Barat are still low. The aim of this research is to determine the influence of the RME (Realistic Mathematic Education) learning model on mathematical communication in students, to determine the influence of self-efficacy on students' mathematical communication abilities, and to determine the interaction between the RME (Realistic Mathematic Education) learning model and self-efficacy. towards students' mathematical communication. This research uses a quantitative research approach, while the type of research used in this research is quasi experimental design. Experimental research was carried out, students received Realistic Mathematics Education (RME)Approach learning treatment and control, namely students received direct instruction learning model treatment. The population in this study were all class VIII students at SMP N 06 Tulang Bawang Barat in TA. 2023/2024, even semester with a sample of 90. Sampling in this study used cluster random sampling. The data analysis technique used two-way ANOVA. Before testing with the ANOVA test, the data used must be normally distributed and homogeneous. Based on the results of data analysis, it can be concluded that: 1) There are differences in the influence of the RME (Realistic Mathematic Education) learning model on mathematical communication among students. 2) There is an influence of self-efficacy on students' mathematical communication abilities. 3) There is an interaction between the RME (Realistic Mathematic Education) learning model and self-efficacy towards students' mathematical communication.